Management of Breast Cancer during Pregnancy: Are We Compliant with Current Guidelines? - Shlensky, Victoria; Hallmeyer, Sigrun; Juarez, Lourdes; Parilla, Barbara V. (American Journal of Perinatology Reports, 2017)
Introduction The purpose of this study was to evaluate the management of patients with breast cancer in pregnancy treated at the Advocate Health Care, to determine whether these patients were treated according to guidelines for pregnant patients, which aim to maximize both fetal and maternal outcomes.Methods A retrospective chart review was performed at the Advocate Lutheran General Hospital, Christ Medical Center, and Illinois Masonic Medical Center from 2002 to 2012 on patients diagnosed with breast cancer during pregnancy using ICD-9 (International Classification of Diseases - 9th version) codes.Results Eleven patients between 12 and 37 weeks' gestation matched the search criteria. One patient terminated the pregnancy. Patients in our study were treated appropriately according to guidelines with the following exceptions. Trastuzumab was used in one patient during pregnancy which likely caused the oligohydramnios resulting in an induction of labor at 33 weeks. Three patients were delivered preterm between 34 and 36 weeks without an obstetric indication. Two patients underwent sentinel node biopsy.Conclusion The diagnosis of breast cancer in pregnancy is an infrequent but devastating diagnosis that is likely to increase. Although sentinel lymph node biopsy is not generally recommended in pregnancy, this may be an outdated guideline as using a low-dose lymphoscintigraphic technique appears to be safe in pregnancy.
Keywords: breast cancer; pregnancy; chemotherapy; sentinel node biopsy